Limbs interweaving for Neotropical anurans - Gonzalves Velasco, Isabel (2025)
Anurans have developed a variety of antipredator behaviors, including aposematism, posturing, and leg interweaving, to enhance survival against predators. Leg interweaving, observed in species like Dendropsophus branneri and D. oliverai, involves crossing limbs and may serve as a displaced behavior rather than a true defense. Unlike species with bright aposematic colors, these frogs rely primarily on camouflage for protection. The variability and limited documentation of leg interweaving highlight the need for further experimental research to clarify its function and significance, contributing to a deeper understanding of the adaptive strategies employed by anurans under predation pressure.